Seroprevalence of Severe Acute Respiratory Syndrome Coronavirus 2-Specific Antibodies in Australia After the First Epidemic Wave in 2020: A National Survey. (31st January 2022) - Vette, Kaitlyn M; Machalek, Dorothy A; Gidding, Heather F; Nicholson, Suellen; O'Sullivan, Matthew V N; Carlin, John B; Downes, Marnie; Armstrong, Lucy; Beard, Frank H; Dwyer, Dominic E; Gibb, Robert; Gosbell, Iain B; et al.
Abstract: Background: As of mid-2021, Australia's only nationwide coronavirus disease 2019 (COVID-19) epidemic occurred in the first 6 months of the pandemic. Subsequently, there has been limited transmission in most states and territories. Understanding community spread during the first wave was hampered by initial limitations on testing and surveillance. To characterize the prevalence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)-specific antibody seroprevalence generated during this time, we undertook Australia's largest national SARS-CoV-2 serosurvey. Methods: Between June 19 and August 6, 2020, residual specimens were sampled from people undergoing general pathology testing (all ages), women attending antenatal screening (20–39 years), and blood donors (20–69 years) based on the Australian population's age and geographic distributions. Specimens were tested by Wantai total SARS-CoV-2-antibody assay. Seroprevalence estimates adjusted for test performance were produced. The SARS-CoV-2 antibody-positive specimens were characterized with microneutralization assays. Results: Of 11 317 specimens (5132 general pathology; 2972 antenatal; 3213 blood-donors), 71 were positive for SARS-CoV-2-specific antibodies. Seroprevalence estimates were 0.47% (95% credible interval [CrI], 0.04%–0.89%), 0.25% (CrI, 0.03%–0.54%), and 0.23% (CrI, 0.04%–0.54%), respectively. No seropositive specimens had neutralizing antibodies. Conclusions: Australia's seroprevalence was extremely low (<0.5%) after the only national COVID-19 wave thus far. These data and the subsequent limited community transmission highlight the population's naivety to SARS-CoV-2 and the urgency of increasing vaccine-derived protection. Abstract : SARS-CoV-2 seroprevalence was very low (<0.5%) in Australia following the first epidemic wave in March-April 2020, demonstrating the success of control measures implemented at the time. Results also emphasize the crucial role of vaccination, as the vast majority of the Australian population had no infection-derived protection against SARS-CoV-2.